Respuesta de vitro-plantas de banano musa spp. variedad valery en la fase de aclimatación de vivero en diferentes sustratos - Ramón Vera, Carlos Geovanny (2014)
In the laboratory of biotechnology from the campus of the Facultad de Ciencias Agropecuarias de la Universidad Tecnica de Machala, started an investigation relative to studying the substrates of organic-minerals for the acclimatization of lab-plants of banana with the following objectives: 1. Determine the effect of different substrates in the acclimatization of lab-plants of banana with foliar fertilization in the nursery phase. 2. Perform an analysis of treatment costs. In accordance of the natural life zones of Holdrege and in the ecological map of Ecuador, the test site corresponds to a really dry tropical forest (bms-T) with an annual average rainfall of 699mm, an annual average temperature of 25°C and a relative percentage of humidity of 84%. Lab-plants of banana Valery variety were employed, bags of polyethylene, substrates of sand, hummus, zeolite and ground corn balance, vernier, flex meter, mesh to 75% of brightness, fertilizer, shovels, wheel barrel, formol and black plastic. The study factors in the present investigation are: sand, hummus, zeolite and ground corn, mixed in different proportions giving result to six treatments, T1 hummus-zeolite-corn maize (5-2.5-2.5); T2 sand-zeolite-ground corn (2.5-5-2.5); T3 sand-hummus-ground corn(2.5-2.5-5.0); T4 sand-zeolite-ground corn (2.5-2.5-2.5); T5 sand-hummus-zeolite (5-2.5-2.5) and T6, controlled sand-hummus-zeolite. The treatments were fixed with a completely random designed with six treatments and three replicas, totalizing 18 experimental units the studied variables of jurisdiction seedling height was until 90 days; diameter of pseudostem weekly until 90 days; number of leaves until 30, 60 and 90 days; foliar area until 90 days; weight of the roots until 90 days and percentage of plants ready for the field. A foliar liquid fertilizer was used chemically balanced with a compound of molecules (phosphates, sulfates and borates very active) of high purity, totally assailable for the plants. The dose used was 12ml diluted in 1lt of water and it was applied every 20 days since the first month of acclimatization. In the statistical analysis and Duncan tests of registered results in weekly frequency, Statistical significance was obtained from the sixth week after planting. The investigated substrates in the rooting of lab-plants from the hybrid of banana Valery formulated with sand, hummus, zeolite, corn cob, in different proportions of three of these components differed significantly when analyzing the independent variables of plant growth, foliar area, number of leaves, diameter of the stem. The control substrate was compounded with 50% sand, 25% hummus and 25% zeolite was statistically superior due to respect with the other studied substrates. The growth in height evaluated in 12 consecutive weeks reached the highest rate of increase in the control substrate (50% of sand, 25% of worm hummus and 25% of zeolite) with 10,64 cm a week. The incorporation of ground corn cob to substrates T1 and T5 and the elimination of hummus in substrates T2 and T4 did not show any satisfactory results during growth and vigor of the plants at the end of the trial.